2015
DOI: 10.1016/j.celrep.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of IL-1-Induced Enhancers Depends on TAK1 Kinase Activity and NF-κB p65

Abstract: The inflammatory gene response requires activation of the protein kinase TAK1, but it is currently unknown how TAK1-derived signals coordinate transcriptional programs in the genome. We determined the genome-wide binding of the TAK1-controlled NF-κB subunit p65 in relation to active enhancers and promoters of transcribed genes by chromatin immunoprecipitation sequencing (ChIP-seq) experiments. Out of 35,000 active enhancer regions, 410 H3K4me1-positive enhancers show interleukin 1 (IL-1)-induced H3K27ac and p6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 47 publications
8
55
0
Order By: Relevance
“…Here, we identify a TNF␣-inducible c-Jun binding region flanking a cluster of four highly TNF␣-regulated chemokine genes. This region has been found to harbor p65 binding sites induced by interleukin-1 (IL-1) in KB cells (40). By quantitative ChIP-PCR, we confirmed the binding of both AP-1 and p65 at this CXC locus.…”
Section: Discussionsupporting
confidence: 56%
“…Here, we identify a TNF␣-inducible c-Jun binding region flanking a cluster of four highly TNF␣-regulated chemokine genes. This region has been found to harbor p65 binding sites induced by interleukin-1 (IL-1) in KB cells (40). By quantitative ChIP-PCR, we confirmed the binding of both AP-1 and p65 at this CXC locus.…”
Section: Discussionsupporting
confidence: 56%
“…Most of the inducible p65 binding sites (3750 sites) are found outside from promoter regions that are only occupied at 635 sites (Fig. 5 C ), a distribution consistent with other studies (15, 36). …”
Section: Resultssupporting
confidence: 89%
“…Direct binding of p65 has been described for the AP-1 family members c-Fos and c-Jun (49). Accordingly, a previous study showed that IL-1–inducible corecruitment of p65 and the AP-1 subunits c-Fos and JunD to the promoters of the NF-κB target genes IL-8 and CXCL2 was dependent on the presence of the p65 protein (15). The auxiliary function of AP-1 binding for strictly NF-κB–dependent expression of the IL-8 gene was also found in this study after mutation of the AP-1 binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we analyzed the amounts of NF-κB subunits in soluble (N1) and chromatin (N2) nuclear fractions in response to HCoV-229E infection or IL-1. Consistent with previously published data, IL-1 strongly increased the concentrations of p50, p52, p65 and c-Rel NF-κB subunits by 5 to 10-fold in the soluble N1 fraction, whereas p65 was the most prominently increased subunit stably associated with the N2 chromatin fraction ( Fig 5A and 5B, S6A Fig) [24,25]. In HCoV-229E-infected cells, a modest 1.5 to 3-fold increase of p65 was observed in the N1 fractions, but also of p50 and p52 which are characteristic for the activation of the non-canonical pathway (Fig 5A and 5B).…”
Section: Modulation Of Nf-κb Signaling By Hcov-229e and Functional Resupporting
confidence: 92%